Dissecting the effects of mtDNA variations on complex traits using mouse conplastic strains - Yu, Xinhua; Gimsa, Ulrike; Wester-Rosenlöf, Lena; Kanitz, Ellen; Otten, Winfried; Kunz, Manfred; Ibrahim, Saleh M. (Genome Research, 2009)
Previous reports have demonstrated that the mtDNA of mouse common inbred strains (CIS) originated from a single female ancestor and that mtDNA mutations occurred during CIS establishment. This situation provides a unique opportunity to investigate the impact of individual mtDNA variations on complex traits in mammals. In this study, we compiled the complete mtDNA sequences of 52 mouse CIS. Phylogenetic analysis demonstrated that 50 of the 52 CIS descended from a single female Mus musculus domesticus mouse, and mtDNA mutations have accumulated in 26 of the CIS. We then generated conplastic strains on the C57BL/6J background for 12 mtDNA variants with one to three functional mtDNA mutations. We also generated conplastic strains for mtDNA variants of the four M. musculus subspecies, each of which contains hundreds of mtDNA variations. In total, a panel of conplastic strains was generated for 16 mtDNA variants. Phenotypic analysis of the conplastic strains demonstrated that mtDNA variations affect susceptibility to experimental autoimmune encephalomyelitis and anxiety-related behavior, which confirms that mtDNA variations affect complex traits. Thus, we have developed a unique genetic resource that will facilitate exploration of the biochemical and physiological roles of mitochondria in complex traits.